A Preliminary Study on Population of Some Passeriformes at Marala Head - Zahid Bhatti; Fakhra Nazir; Asad Ghufran (Journal of Bioresource Management, 2019)
Passerines are perching birds of order Passeriformes representing half of the diversity of birds (Sibley and Monroe, 1990). There are total 6,600 species identified under 140 families declaring Passeriformes as the largest order of birds. Three hundred and thirteen species of Passeriformes were reported by Roberts (1992) from Pakistan but according to check list of birds of Pakistan there are more than 400 species of Passeriformes in Pakistan (Clements, 2019). They have significant ecological importance in an ecosystem and are mostly omnivores except the shrikes which are carnivorous. This study was done to form a preliminary checklist of Passeriformes at Marala Wetlands from October 2000 to September 2001. Census of the passeriformes was conducted on monthly basis by physically exploring the starting points from the three rivers (Kikar post, Kalyal and Rangpur Kuri) to Marala Head. Four families (Dicruridae, Passeridae, Ploceidae and Sylviidae) belonging to the order of Passeriformes were observed. Only one species was observed from each family.